The Using Confirmatory Factor Analysis as Construct Validity in Education Research: A Analysis with Biblioshiny - Zafrullah, Zafrullah; Atika Miftah Ramadhani; Rizki Tika Ayuni; Nuansa Trimaya Fadhilla; Rina Safitri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims at bibliometric analysis on the topic of confirmatory factor analysis in the field of education. Researchers used the RStudio and Vosviewer applications to map bibliometrics results. From the results of the analysis that has been carried out, it is concluded that overview of the bibliometric analysis of 203 research documents, published between 1987 and 2023, from various sources in the Scopus database. Publication growth shows an increase of 7.61% every year. In contrast, it saw a peak in growth in 2018, with 24 publications, reflecting significant research interest and focus. The University of Tasmania from Australia dominates with 13 articles. Nurse Education Today was the highest contributing journal, contributing 7 articles, highlighting the important role of nursing in this research. This analysis illustrates the diversity of contributions of researchers from various institutions in Thailand in the exploration of CFA in education. The highest document citation is